COMPARISON OF ENDOTHELIAL CELL COUNT BEFORE AND AFTER PHACOEMULSIFICATION IN GRADE 2 NUCLEAR SCLEROSIS CATARACT VERSUS GRADE 4 NUCLEAR SCLEROSIS CATARACT (Journal of Medical & Health Sciences Review, 2025)
Background: Phacoemulsification is a frequent cataract surgery method nowadays. The loss of corneal endothelial cells during phacoemulsification is influenced by the degree of nucleus sclerosis. Irrigation flow, fluid turbulence and movement, air bubbles, direct trauma from instruments or lens fragments, and the time and power required to complete nuclear emulsification are other factors that might result in endothelial cell injury during phacoemulsification.Methods: Our study included 90 patients after taking approval from Ethical Review Committee from 1st May 2024 to 31st October 2024. Patients were selected for the data collection process in the Eye outpatient department. Slit lamp examination was performed on all patients to diagnose cataract. Spectrum microscopy was done to examine endothelial cell count before and after phacoemulsification in grade 2 versus grade 4 nuclear sclerosis cataract. Patients were divided into two groups based on the grade of nuclear sclerosis cataract: Group A (patients with grade 2 nuclear sclerosis cataract) and Group B (patients with grade 4 nuclear sclerosis cataract).Results: The mean age of patients was 61.311±3.97 years in Group A and 62.400±3.58 years in Group B. The mean ±SD of baseline endothelial cell count in Group A was 2248.022 ±132.05 mm2 while in Group B was 1977.488 ±180.90 mm2 (p-value